PENGARUH KOMPETENSI APARATUR PEMERINTAH, PENGENDALIAN AKUNTANSI, SISTEM PELAPORAN, KEJELASAN SASARAN ANGGARAN DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJAINSTANSI PEMERINTAH (Studi Empiris pada Satuan Kerja Perangkat Daerah Kabupaten Kampar) - Rizka Aulia Putri; Restu Agusti; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to analyze and gets empirical prove of competence government officials , accounting control , the reporting system , clarity the budget and observance of legislation over the accountability performance government agencies. Population of this research was Working Units (SKPD) at Kampar. Respondents in this study is the structural officials involved in drafting the budget. In total of 33 SKPD will be given three questionnaires, so the number of questionnaires distributed is 76 pieces. The data used are primary data. Data Collection Techniques of field research and literature. The analytical method used in this research is multiple regression analysis. The results prove that Adherence to Government Regulations no signicant effect on performance accountability of government agencies, this is indicated from its significance value more than 0.05. While competence government officials , accounting control , the reporting system , clarity the budgethas a significant effect on on performance accountability of government agenciesby0.005.Keywords :Competence, Management Accounting, Reporting Systems, Clarity Goal, Obedience, Accountability